A Foucauldian analysis of literary text selection practices and educational policies in Ontario, Canada. Issue 3 (3rd May 2016) - Greig, Christopher J.; Holloway, Susan M.
Abstract : Like schools, curricula are socially constructed and constituted within broader social, political, and historical relations of power, powerfully shaping students' beliefs and attitudes about themselves and their relationship toward the world. In light of this, the importance of literature selection cannot be overstated. School-sanctioned texts often provide the core curriculum, and secondary school English teachers rely on them heavily. The self-regulatory practices a teacher engages in will shape not only how the teacher begins to understand the self, but also works to construct an 'appropriate' teacher identity. Using a Foucauldian theoretical lens, this paper draws upon findings from a synthesis of school board policies and interviews with English teachers and department heads in Ontario, Canada, to explore the discursive practices that shape literary text selection.